Coalescence, the thermal model and multi-fragmentation: the energy and volume dependence of light nuclei production in heavy ion collisions. (1st May 2022) - Hillmann, Paula; Käfer, Katharina; Steinheimer, Jan; Vovchenko, Volodymyr; Bleicher, Marcus
Abstract: We present results of a phase space coalescence approach within the UrQMD transport and -hybrid model for a very wide range of beam energies from SIS to LHC. The coalescence model is able to qualitatively describe the whole range of experimental data with a fixed set of parameters. Some systematic deviations are observed for very low beam energies where the role of feed down from heavier nuclei and multi-fragmentation becomes relevant. The coalescence results are mostly very close to the thermal model fits. However, both the coalescence approach as well as thermal fits are struggling to simultaneously describe the triton multiplicities measured with the STAR and ALICE experiment. The double ratio of tp / d 2, in the coalescence approach, is found to be essentially energy and centrality independent for collisions of heavy nuclei at beam energies of E lab > 10 A GeV. On the other hand the clear scaling of the d / p 2 and t / p 3 ratios with the systems volume is broken for peripheral collisions, where a canonical treatment and finite size effects become more important.